Effect of different Gamma Rays doses on Seed Germination, Seedling parameter on local seed okra (Abelmoschus esculentus (L.) - Hassoon, Wafaa Hadi; Dheyab, Naeem Saeed; Abd Alsada, Ali Jabbar (Journal of agricultural, environmental and veterinary sciences, 2024)
The experiment was carried out to study the effect of different gamma irradiation in 100 -800 Gy with non-irradiated control on seed okra [Abelmoschus esculentus (L.). The study carried in Microbiology Dept. Directorate of Agricultural Research. Ministry of Science and Technology in 2020. The results showed that 100-300 Gy had positive effects with respect to all studied growth seeding parameters. With increase in radiation above 300 Gy a decreasing  germination potential, The lowest germination percentage was recorded at 800Gy,speed of germination was noted by Control (10.00 day) followed by gamma irradiation dose  800(9.90 day) and the same dose was  logged  lowest mean daily germination (7.85 seed day-1 ),  higher doses (800,700,600 ) Gy  marked reduction in root, shoot  length, vigor index , chlorophyll a chlorophyll b .and total chlorophyll. The result showed a decreasing of the fresh weight of okra when radiation dose was increased   While, dry weight was increasing when the radiation dose was increased. This study shows that the low dose gamma radiation may enhance the germination rate and the seedling growth during the early seedling state of okra seeds.
Keywords: Gamma Irradiation; Germination Percent; Vigor Index; Chlorophyll; Abelmoschus esculentus